Axial length and refraction errors in premature infants with and without retinopathy of prematurity - S.V. Katsan; A.A. Adakhovskaia (Ukrainian Society of Ophthalmologists, 2019)
Background. Preterm children, to a greater extent, can be affected by myopia in infancy and early childhood. Refractive errors can be related to the irregular growth of the eye. Purpose. To assess the incidence of refractive errors in groups of premature infants, aged 1 to 3 years, without ROP, with regressed ROP, and ROP treated with laser photocoagulation (LP). Material and Methods. Ophthalmological examination findings of 175 premature infants were studied. At the age of 4-5 weeks, the children were examined for ROP. Within the period between 6 months and 3 years, the children underwent standard ophthalmological examination and ultrasound diagnosis through closed eyelids. The findings were analyzed in three groups based on the main diagnoses: group 1, children without ROP; group 2, children with spontaneously regressed ROP; group 3, children with ROP, treated with retinal laser photocoagulation of avascular zones. MedCalc v.17.4 (MedCalc Software bvba, 1993-2017) was used to statistically process the data. Results. In 111 children (63%) of group 1, axial length (AL) of the right and left eyes was 19.3±1.1 mm and 19.4±1.1 mm, respectively. Hyperopia was noted in the right eye in 104 children (93.7%) and in the left eye in 105 children (94.6%). In 42 children (24%) of group 2, AL was 19.2±1.2 mm and 19.2±1.3 mm in the right and left eyes, respectively. Hyperopia was noted in the right eyes in 39 children (92.9%) and in the left eye in 37 children (88.1%). In 22 children (13%) of group 3, AL of the right and left eyes was 18.6±1.1 mm and 18.8±1.2 мм, respectively. Myopia was noted in the right eye in 6 children (27.3%) and in the left eye 3 children (13.6%); hyperopia was noted in the right eye in 11 children (50%) and in the left eye in 12 children (54.6%); emmetropia was in the right eye in 1 child (4.5%) and in the left eye in 2 children (9,1%); and astigmatism was in the right eyes in 4 children (18.2%) and in the left eye in 5children (22.7%). Conclusions. It was found that axial length in preterm children at the age of 1-3 years with a history of LP for ROP was smaller than that in children without ROP and with regressed ROP (18.7 mm versus 19.35 mm and 19.2 mm, respectively). The incidence rates of myopia (20.45%) and astigmatism (20.45%) were higher in preterm children with LP-treated ROP as compared to children without ROP (4.95% and 2.7%, respectively) and with regressed ROP (8.3% and 1.2%, respectively).